Energy Justice Across Borders - Bombaerts, Gunter; Jenkins, Kirsten; Sanusi, Yekeen A.; Guoyu, Wang (Springer Nature, 2020)
Philosophy; Engineering ethics; Energy policy; Energy and state; Economic geography; Renewable energy resources; Sustainable development; Energy systems